De la recommandation à l’imposition normative - Clémentine Belle Grenier (Cahiers Jean Moulin, 2020)
The study of the French Constitutional Council’s archives enables us to consider the presidential election from a rare perspective: the unsuccessful attempts to become a presidential candidate. From mere applications in a few words to detailed letters of presentation comprising lots of precisions about private and professional life, many people write to the Council to declare their intention to race for the presidency. Through their self-presentations, we try to analyse their representation of the presidential duty and of the president as a socially constructed rolemodel. This article also aims to examine the role of the Constitutional Council in the shaping of this representation of the president through its role as election judge and adviser. The purpose is to show how an institution contributes to the enforcement of the conditions of access to the first round of the election thanks to its legals recommandations. It also shows how the law affects the behaviour of the candidates.